A study of the effect of Mn on the precipitation and phase transition of nanoscale Cu-rich phase in Fe–Cu alloys by phase-field method - Mingguang Wei; Tongguang Zhai; Yong Xu; Yingming Tu; Haisheng Han (Journal of Materials Research and Technology)
In this study, the influence of Mn content on the precipitation and structural phase transition of the Cu-rich phase in Fe–Cu–Mn alloy at 773 K was simulated by a phase-field model. The results showed that, in the early stage of the precipitation, Mn and Cu atoms were first congregated to form Mn–Cu co-clusters, followed by Mn atoms separating from the co-clusters to segregate at the cluster-matrix interface to form a Cu-rich core and Mn-rich shell structure once the Cu content in the co-clusters reached 85%. The increase in Mn content in the alloy promoted the nucleation of the Cu-rich phase, resulting in an increase in the number density and volume fraction of the Cu-rich precipitates, while inhibiting the growth and coarsening of the Cu-rich phase. Furthermore, as the Mn content increases, the incubation time required for α-Cu phase to transform into the 9R phase was increased, while the critical radius for the transformation of α-Cu precipitates into 9R phase was decreased.